2022
DOI: 10.1093/nar/gkac494
|View full text |Cite
|
Sign up to set email alerts
|

TBX2 acts as a potent transcriptional silencer of tumour suppressor genes through interaction with the CoREST complex to sustain the proliferation of breast cancers

Abstract: Chromosome 17q23 amplification occurs in 20% of primary breast tumours and is associated with poor outcome. The TBX2 gene is located on 17q23 and is often over-expressed in this breast tumour subset. TBX2 is an anti-senescence gene, promoting cell growth and survival through repression of Tumour Suppressor Genes (TSGs), such as NDRG1 and CST6. Previously we found that TBX2 cooperates with the PRC2 complex to repress several TSGs, and that PRC2 inhibition restored NDRG1 expression to impede cellular proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…While we did test two direct DNA-binding proteins-GFI1 and HMG20B-other repressive components, like Phf21b, INSM1, Pax2, TBX2, and SNAI2, have been reported as KDM1A partners in different tissues and might contribute to NDRG1 repression as well. [36][37][38][39][40] Although NDRG1 has been initially characterized as a tumor suppressor, its roles seem to be highly contextual, such that in certain tissues it may even exhibit tumor promoting effects. [41,42] Our transcriptome analysis showed that NDRG1 upregulation induced an inhibition of Wnt signaling that was accompanied by a marked reduction of cycling cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did test two direct DNA-binding proteins-GFI1 and HMG20B-other repressive components, like Phf21b, INSM1, Pax2, TBX2, and SNAI2, have been reported as KDM1A partners in different tissues and might contribute to NDRG1 repression as well. [36][37][38][39][40] Although NDRG1 has been initially characterized as a tumor suppressor, its roles seem to be highly contextual, such that in certain tissues it may even exhibit tumor promoting effects. [41,42] Our transcriptome analysis showed that NDRG1 upregulation induced an inhibition of Wnt signaling that was accompanied by a marked reduction of cycling cells.…”
Section: Discussionmentioning
confidence: 99%
“…While we did test two direct DNA‐binding proteins—GFI1 and HMG20B—other repressive components, like Phf21b, INSM1, Pax2, TBX2, and SNAI2, have been reported as KDM1A partners in different tissues and might contribute to NDRG1 repression as well. [ 36–40 ]…”
Section: Discussionmentioning
confidence: 99%
“…Having identified GR as a novel interactor of TBX2 in CRPC, we next sought to investigate the possibility of pharmacologically targeting the TBX2-GR interaction. Previous studies have identified an interaction between TBX2 and LSD1 as a part of the COREST complex 17 . These reports also identified that the interaction between TBX2 and LSD1 could be pharmacologically targeted through the LSD1 inhibitor SP2509 17 , and that disruption of the TBX2-LSD1 interaction resulted in the inhibition of TBX2 downstream targets 17 .…”
Section: Sp-2509 An Allosteric Lsd1 Inhibitor Impedes Tbx2-gr Physica...mentioning
confidence: 98%
“…Previous studies have identified an interaction between TBX2 and LSD1 as a part of the COREST complex 17 . These reports also identified that the interaction between TBX2 and LSD1 could be pharmacologically targeted through the LSD1 inhibitor SP2509 17 , and that disruption of the TBX2-LSD1 interaction resulted in the inhibition of TBX2 downstream targets 17 . Further, and of relevance to our study, another report showed that LSD1 is upregulated in CRPC 44,45 .…”
Section: Sp-2509 An Allosteric Lsd1 Inhibitor Impedes Tbx2-gr Physica...mentioning
confidence: 98%
“…ZNF217 negatively regulates the expression of EPB41L4A-AS2 at the transcriptional level, most probably through the enhanced recruitment of EZH2 and increased H3K27me3 enrichment at EPB41L4A-AS2 locus [ 67 ]. A recent study identified a new tumor-suppressive lncRNA, namely LINC00111, whose transcription is negatively regulated by the TXB2 transcriptional complex [ 106 ]. In BCa cells, ZNF217 was identified to be a novel interactor of TBX2 that binds to 30% of TXB2-bound promoters, including that of the lncRNA LINC00111.…”
Section: Noncoding Rna Network Target Znf217 Mrna ...mentioning
confidence: 99%